ACE2 mediates tryptophan alleviation on diarrhea by repairing intestine barrier involved mTOR pathway - Jinze Li; Yingli Yan; Yang Fu; Zhe Chen; Yongjie Yang; Yu Li; Jie Pan; Feiwu Li; Cuifang Zha; Kai Miao; Lukuyu, Ben A.; Kashif Saleemi, M.; et al. (BioMed Central, 2024)
The membrane-delimited receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), angiotensin-converting enzyme 2 (ACE2), which is expressed in the intestine, collaborates with broad neutral amino acid transporter 1 (B0AT1). Tryptophan (Trp) is transported into intestinal epithelial cells by ACE2 and B0AT1. However, whether ACE2 and its binding protein B0AT1 are involved in Trp-mediated alleviation of intestinal injury is largely unknown. Here, we used weaned piglets and IPEC-J2 cells as models and found that ACE2/B0AT1 alleviated lipopolysaccharide (LPS)-induced diarrhea and promoted intestinal barrier recovery via transport of Trp. The levels of the aryl hydrocarbon receptor (AhR) and mechanistic target of rapamycin (mTOR) pathways were altered by ACE2. Dietary Trp supplementation in LPS-treated weaned piglets revealed that Trp alleviated diarrhea by promoting ACE2/B0AT1 expression, and examination of intestinal morphology revealed that the damage to the intestinal barrier was repaired. Our study demonstrated that ACE2 accompanied by B0AT1 mediated the alleviation of diarrhea by Trp through intestinal barrier repair via the mTOR pathway.